Building Purchase Intention By Understanding Interaction, Intimacy, Attitude and Intention to Play Shopee Games - Zevaniya Vika Radiliana; Atmaja, Ferry Tema (TIJAB (The International Journal of Applied Business), 2024)
Background: The discourse on gamification continues to be relevant in contemporary times. This concept has rapidly emerged as an innovative trend within the marketing domain. Business practitioners increasingly view the application of gamification as a novel tool or approach to assess their market potential. Additionally, gamification is perceived as having the capacity to enhance the value of a service. Although discounts continue to be a primary draw, the burgeoning popularity of online shopping platforms can be attributed to the incorporation of entertainment features and gamification elements. Objective: This study discusses the unexplored relationship between gamification and e-commerce, with a focus on interaction, intimacy, attitudes, and gaming intentions in the context of games on e-commerce platforms. Method: This research was conducted through a Google Form questionnaire given to 127 active participants at Shopee Games, and analyzed using SmartPLS 3 software. Results: This research identifies interaction as an important factor that shapes user intimacy and fosters positive attitudes toward platform engagement. Additionally, gaming intention emerged as a significant correlate, influencing increased exposure to in-game product promotions and potentially motivating users in their purchasing intentions. Conclusion: These findings deepen our understanding of the complex relationships between interaction, intimacy, attitudes, gaming intentions, and shopping behavior on e-commerce platforms, thereby offering insights for the development of marketing strategies in the gamification paradigm. This research contributes to the growing understanding of the synergy between gamification and e-commerce.   Keywords: intention to purchase; interaction; intimacy; attitude toward play; play intention.